Determination of the Density and Intensity of Irrigation of Forest Combustible Material before the Combustion Front When Creating an Effective Control Line - Volkov R. S. Roman Sergeevich; Kuznetsov G. V. Geny Vladimirovich; Osipov K. Yu. Konstantin Yuryevich; Khasanov I. R. Irek Raviljevich (2020, 2020)
Title screen